How do students assess the sustainability of their university? A comparison between Dutch and Romanian students from business schools - Florentin Popescu; Tudor Edu; Costel Negricea; Razvan Zaharia; Rodica Milena Zaharia (Amfiteatru Economic Journal, 2020)
This article is exploratory in its essence and aims to analyse the sustainability of universities in the case of three higher education institutions: one university from the Netherlands and two universities from Romania. The main focus is on the awareness of the sustainable university concept among students and on the perception students have about their university: do they consider their university as being a sustainable one? Why? Do they consider they are educated to act as future sustainable business persons? There is a growing interest in researching students' perceptions on the sustainability of universities. Students are the key stakeholders; they represent the future business people, employees, managers or entrepreneurs, responsible for sustainable development. Therefore, universities have to build a "sustainable mindset" for their graduates. This research related to students' perception on sustainable university has two phases. The first one involved a secondary data analysis, based on the online information provided by the universities, in order to assess the sustainability of these universities considering the adapted Deming spiral (planning, operating, reporting and innovating). The second phase involved a qualitative research among students from these three universities, based on focus groups, about the awareness of the sustainable university concept, how they perceive their university from the sustainability point of view and how prepared they consider to be to act as future sustainable persons. Comparisons between universities are performed. The conclusions discuss possible solutions for universities to become more sustainable, and good practices that can be shared among universities are identified.
Keywords: Q01; Q56; I29; 330; sustainable university; sustainable development; students' opinion; Netherlands; Romania